Radiology Case Study - Right-Sided Aortic Arch: An Anomalous Vascular Configuration - Sulejmani, Haris; Nikolova, Sonja (My University, 2024)
Right-sided aortic arch (RAA) is a rare anatomical variant, often discovered incidentally during imaging studies. We present a comprehensive case study of a 77-year-old male with an asymptomatic RAA, emphasizing the crucial role of multimodal imaging in accurate diagnosis. This report explores the imaging findings, potential clinical implications, and the significance of identifying such anomalies for patient management. Right-sided aortic arch (RAA) is an uncommon congenital anomaly characterized by the aorta's deviation to the right of the trachea. While often asymptomatic, its recognition is vital for understanding associated vascular anomalies and potential clinical implications. This case study delves into the imaging nuances, embryological basis, and clinical considerations associated with RAA with mirror image branching of the arch vessels, contributing valuable insights to the existing medical literature. Multidetector computed tomography (MDCT) revealed a right-sided aortic arch with mirror-image branching of the arch vessels. The arch descended on the right side of the trachea, forming a vascular ring.The anomalous arrangement of the left common carotid artery originating from a left brachiocephalic trunk together with the left subclavian artery.Diagnosis: Right-sided aortic arch with mirror-image branching. The embryological basis of RAA involves intricate processes leading to abnormal arch regression and persistence of the right dorsal aorta. The clinical significance lies in potential complications, including tracheal compression and vascular ring formation. Accurate diagnosis through advanced imaging allows for informed decision-making and appropriate patient management. Right-sided aortic arch is a rare anatomical variant that warrants attention due to its potential clinical implications. Awareness of such anomalies and their associated vascular configurations is essential for providing optimal patient care. This case contributes to the limited literature on RAA, emphasizing the importance of thorough imaging in unraveling complex vascular variations. Key words: Right-sided aortic arch,multidetector computed tomography,diagnosis.
Keywords: Right-sided aortic arch; multidetector computed tomography (MDCT); Diagnosis